Preschool Weight and Body Mass Index in Relation to Central Obesity and Metabolic Syndrome in Adulthood - Graversen, L; Sorensen, TIA; Petersen, L; Sovio, U; Kaakinen, M; Sandbaek, A; Laitinen, J; Taanila, A; Pouta, A; Jarvelin, M-R; Obel, C (PLoS ONE, 2014)
Background: If preschool measures of body size routinely collected at preventive health examinations are associated with adult central obesity and metabolic syndrome, a focused use of these data for the identification of high risk children is possible. The aim of this study was to test the associations between preschool weight and body mass index (BMI) and adult BMI, central obesity and metabolic alterations. Methods: The Northern Finland Birth Cohort 1966 (NFBC1966) (N = 4111) is a population-based cohort. Preschool weight (age 5 months and 1 year) and BMI (age 2–5 years) were studied in relation to metabolic syndrome as well as BMI, waist circumference, lipoproteins, blood pressure, and fasting glucose at the age of 31 years. Linear regression models and generalized linear regression models with log link were used. Results: Throughout preschool ages, weight and BMI were significantly linearly associated with adult BMI and waist circumference. Preschool BMI was inversely associated with high-density lipoprotein levels from the age of 3 years. Compared with children in the lower half of the BMI range, the group of children with the 5% highest BMI at the age of 5 years had a relative risk of adult obesity of 6.2(95% CI:4.2–9.3), of adult central obesity of 2.4(95% CI:2.0–2.9), and of early onset adult metabolic syndrome of 2.5(95% CI:1.7–3.8). Conclusions: High preschool BMI is consistently associated with adult obesity, central obesity and early onset metabolic syndrome. Routinely collected measures of body size in preschool ages can help to identify children in need of focused prevention due to their increased risk of adverse metabolic alterations in adulthood.